Understanding food selection and dieting patterns: type 2 diabetes mellitus patients and their families - Dikha Ayu Kurnia (Publishing House Zaslavsky, 2021)
Background. The prevalence of type 2 diabetes mellitus (T2DM) is increasing from year to year, especially in Indonesia. The risk of T2DM starts at the dinner table in the family. Meal planning plays an important role in reducing the potential complications associated with poor glycemic, lipid and blood pressure control. Focusing on reducing sugar, fat and sodium intake and incorporating culture-appropriate foods will improve adherence. However, T2DM patients develop conflicting eating disorders in which there is a gap between nutrition and self-fulfillment regarding eating control. The purpose of this research is to explore the understanding of the diabetes patient and their family in determining the selection of food and eating pattern during the disease. Materials and methods. This study explores the understanding of T2DM patients and their families in the Depok and Jakarta. The purposive sampling method used 14 participants and 7 family members. The data obtained from participant observation and in-depth interviews then analyzed using thematic analysis. Using a descriptive phenomenological method with a semi structured in-depth interview. The interviews were conducted face to face from October 2017 — July 2018 and were analyzed by thematic analysis Collaizi’s method. Results. This study found 4 important themes: 1) food is believed to affect high blood sugar; 2) changes in diet after diabetes; 3) the main concern of the family is to keep eating but not make it a burden; and 4) the challenge faced by participants and their families is the lack of information. This study recommends continuing education and partnerships from nurses about the importance of the relationship between diet and blood glucose levels. Conclusions. People are inclined to rely on simple strategies that limit search when making food choices. The ability of patients and families regarding food ingredients to maintain blood sugar stability is the concern of nurses in providing nutritional education. Food labels can (and to some extent do) provide a wide variety of desirable information, ranging from food content to production details, the food’s carbon footprint, and its origins.